Wild Edible Plant Resources Used by the Mizos of Mizoram, India - Kar, A.; Bora, D.; Borthakur, S.K.; Goswami, N. K.; Saharia, D. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The present communication deals with the wild edible plant resources of Mizo people. Study documented botanical name, family, local name, parts used and mode of preparation along with their parts sold in the local market and their prevailing prices. A total of 279 plant species belonging to 100 families were reported from the study area and out of these 35 species are sold in the market (Bara bazar). Present finding suggest further investigation on nutritional and commercial aspects, pharmacological prospects and conservational needs.